Debate and dialogue : Alain Chartier in his cultural context - Cayley, E (2003)
In early humanist France two debating traditions converge: one literary and vernacular, one intellectual and conducted mainly via Latin epistles. In this thesis I demonstrate how the two fuse in the vernacular verse debates of Alain Chartier, secretary and notary at the court of Charles VII. In spite of considerable contemporary praise for Chartier, his work has remained largely neglected by modern critics. I show how Chartier participates in a movement that invests a vernacular poetic with moral and political significance, inspiring such social engagements as the fifteenth-century poetic exchange known as the Querelle de la Belle Dame sans mercy. I set Chartier in the context of a late-medieval debating climate through the use of a new model of participatory poetics which I term the collaborative debating community. This is a dynamic and generative social grouping based on Brian Stock's model of the textual community, as well as Pierre Bourdieu's sociological categories of field, habitus and capital. This dialectical model takes account of the socio-cultural context of literary production, and suggests the fundamentally competitive yet collaborative nature of late-medieval poetry. I draw an analogy here between literary debates and game-playing, engaging with the game theory of Johan Huizinga and Roger Caillois, and discuss the manuscript context of such literary debates as the materialisation of this poetic game. The collaborative debating community I postulate affords unique insights into the dynamics of late-medieval compositional and reading practices.